2009
DOI: 10.1097/icl.0b013e318199aff6
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an Extraction Solvent Used to Quantify Albumin Deposition on Hydrogel Contact Lens Materials

Abstract: Although TFA/ACN is efficient at extracting albumin deposited on etafilcon lenses, it does not extract all the albumin that is deposited on SH lenses and alternative extraction procedures should be sought.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…Numerous studies evaluating chemical extractants on conventional hydrogels 11, 13, 14, 19, 3136 and, most recently, silicone hydrogel lenses, 9, 10, 14, 15, 19, 30, 37–39 have been reported in the scientific literature. The majority of the research has primarily focused on two used in this study: urea buffer 13 and TFA/ACN.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies evaluating chemical extractants on conventional hydrogels 11, 13, 14, 19, 3136 and, most recently, silicone hydrogel lenses, 9, 10, 14, 15, 19, 30, 37–39 have been reported in the scientific literature. The majority of the research has primarily focused on two used in this study: urea buffer 13 and TFA/ACN.…”
Section: Discussionmentioning
confidence: 99%
“…Final SDS concentrations during incubation were 0.02%, 0.04%, 0.08%, and 0.16%, and lactoferrin was used at its normal in vivo concentration (1.7 mg/mL). 1,39 After incubation and native-PAGE, we found that the banding pattern for lactoferrin protein was markedly altered for protein exposed to 0.16% and 0.08% SDS but not at the lower SDS concentrations (Fig. 1A); at lower levels of SDS and in control samples, the protein was observed to produce a single band; after treatment with higher levels of SDS, two bands were observed, running above and below the normal banding position (Fig.…”
Section: Effect Of Sodium Dodecyl Sulfate Incubation On Tear Protein mentioning
confidence: 87%